PEDAGOGICAL CONSIDERATIONS FOR DEVELOPING KNOWLEDGE OF THE HISTORY OF UZBEK MUSIC AMONG FUTURE MUSIC TEACHERS (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical and methodological foundations of developing knowledge about the history of Uzbek music among future music teachers, the parameters of developing knowledge about the history of Uzbek music among future music teachers, the effectiveness of developing knowledge about the history of Uzbek music among future music teachers. Also, the pedagogical implications of developing knowledge about the history of Uzbek music among future music teachers are analyzed.